2022
DOI: 10.1002/mp.16081
|View full text |Cite
|
Sign up to set email alerts
|

VTDCE‐Net: A time invariant deep neural network for direct estimation of pharmacokinetic parameters from undersampled DCE MRI data

Abstract: To propose a robust time and space invariant deep learning (DL) method to directly estimate the pharmacokinetic/tracer kinetic (PK/TK) parameters from undersampled dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) data. Methods: DCE-MRI consists of 4D (3D-spatial + temporal) data and has been utilized to estimate 3D (spatial) tracer kinetic maps. Existing DL architecture for this task needs retraining for variation in temporal and/or spatial dimensions. This work proposes a DL algorithm that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the last few years, deep learning (DL) techniques have been actively explored for applications in medical imaging (8), such as image registration, spatial super-resolution, denoising, and disease prediction. Several studies investigated the potential of applying DL to DCE-MRI, including tumor segmentation (9), therapy response prediction for cancer (10), lesion malignancy classification (11), and pharmacokinetic parameter estimation from time-resolved DCE-MRI (12)(13)(14)(15)(16)(17). These studies demonstrated the capability of DL to extract information and simplify postprocessing, as well as the growing interest in pharmacokinetic modeling.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, deep learning (DL) techniques have been actively explored for applications in medical imaging (8), such as image registration, spatial super-resolution, denoising, and disease prediction. Several studies investigated the potential of applying DL to DCE-MRI, including tumor segmentation (9), therapy response prediction for cancer (10), lesion malignancy classification (11), and pharmacokinetic parameter estimation from time-resolved DCE-MRI (12)(13)(14)(15)(16)(17). These studies demonstrated the capability of DL to extract information and simplify postprocessing, as well as the growing interest in pharmacokinetic modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Kettelkamp et al 29 also estimated the PK parameters from fully sampled DCE-MRI data with explicit knowledge of AIF. Rastogi et al 30 have recently proposed an adaptive model with different architecture to address the issues of the information retention (spatiotemporal dimension) requirement as well as the need for the AIF information for PK parameter estimation. They proposed a 2.5D Unet-based architecture for direct estimation of the PK parameters from under-sampled k-t space.…”
Section: Introductionmentioning
confidence: 99%